Anti-Diabetic and Anti-Oxidant Activity of Leaf and Bark Extracts of Murraya koenigii on Streptozotocine Induced Diabetic Rats - Sahu, P.K.; Jena, R.C.; Jena, S.; Panda, A.; Bhol, R. (Asian Journal of Chemistry, 2013)
The anti-hyperglycemic and anti-oxidant activity of leaves and bark extracts (aqueous, methanolic, chloroform and n-hexane) of Murraya koenigii was evaluated on streptozotocin induced diabetic in wistar albino rats. The leaf and bark extract was demonstrated LD50> 3 g/kg and LD50 > 3.6 g/kg respectively with low toxicity. Remarkable loss body weight retrieval (+14.37 g) was demonstrated by using Murraya koenigii leaf aqueous extract. Among all the different polarity of leaf and bark extracts, the aqueous and methanolic leaf extract at the dose levels of 300 mg/kg body weight produced a significant decrease in fasting blood glucose level by 64.16 and 60.84 % respectively with respect to initial fasting blood glucose level after 15 days of the treatment. In the oral glucose tolerance test, the aqueous and methanolic leaf extracts at the dose levels of 300 mg/kg was also effective that decreased glycemia (2.7 % and 2.1 %) at 1 h and the effect persisted unit at 2 h. (p < 0.05) after glucose loading, which revealed impaired glucose tolerance. Aqueous leaf extract demonstrated highest DPPH free radical scavenging activity at 89.32 ±1.65 than the methanolic, chloroform and n-hexane extracts 76.34 ± 1.56, 67.89 ± 1.54 and 59.56 ± 1.32 respectively at a concentration of 100 μg/mL. Beside this aqueous leaves extract also revealed highest Ferric-reducing antioxidant power assay value i.e. 76.32 ± 1.87 than the other extracts at a concentration of 100 μg/mL. For all the estimated parameters used with leaf and bark the results of the aqueous leaf extract treated groups were restored to the near normal level, there by indicating good anti-hyperglycemic activity of the leaf aqueous extract of Murraya koenigii.